Biosynthesis of very long chain fatty acid-containing psphingolipids in germinal cells - Furland, Natalia Edith (2011)
In mammalian testis, sphingomyelin (SM) and ceramide (Cer) were previously shown to be rich in very long chain (VLC) polyunsaturated fatty acids (PUFA). Recent work in rat pachytene spermatocytes and round spermatids demonstrated that these sphingolipids exclusively belong to germ cells. We also recently showed that these two cell types, highly enriched in 22:5n-6- containing glycerophospholipids, express mRNA transcripts of ELOVL5 and ELOVL2, two elongases involved in the biosynthesis of C18-C22 PUFA. Because such type of PUFA need to be further elongated to produce the VLCPUFA present in rat testicular sphingolipids (C26-C32), in this work we studied the expression of ELOVL4, the enzyme expected to catalyze such elongation. During postnatal development, ELOVL4 protein expression was first detectable in the rat testis at P25, in concomitance with the timing of appearance of the first spermatocytes. In adult rat seminiferous tubules, whereas the expression of this elongase was found to be only marginal in Sertoli cells, it was significant in spermatocytes and spermatids. The use of radiolabeled precursors and the fluorescent marker NBD C6-Cer showed that isolated spermatogenic cells in culture do synthesize sphingolipids. Both results are consistent in demonstrating that spermatogenic cells are able to biosynthesize the molecular species of SM and Cer that contain VLCPUFA.